ANTIBACTERAIL ACTIVITY OF ZnO AND Na / ZnO NANOROD ARRAY - J. Jasim, Fattima Al-Zahraa; A-Ali Draea, Abbas; J-Eweadh, Mufeed (International Journal of Psychosocial Rehabilitation, 2020)
A novel method was used for synthesized Na/ZnO nanorods. Various techniques were used to determine the structural properties of pure and loaded ZnO Nanorods such as X-ray diffraction (XRD) , Scanning electron microscopy (SEM) , Energy dispersive spectra( EDS) and Atomic force microscope (AFM). Also biological activity was studied through bacterial inhibition of nanorods against gram positive (Pseudomonas) and gram negative (Staphylococcus aureus) were measured by total account of bacteria technique The results show that the antibacterial activity was inhibited by using Na/ ZnO nanorods compared to the activity of pure ZnO NPs. The mechanism of microbial inhibition in presence of pure and loaded ZnO nanorods in aqueous solution was suggested.